A systematic review and meta‐analysis of group psychotherapy for sub‐clinical depression in older adults. (12th November 2012) - Krishna, Murali; Honagodu, Abhijit; Rajendra, Rajgopal; Sundarachar, Rajesh; Lane, Steven; Lepping, Peter
<x xml:space="preserve">Abstract</x> Objectives Studies investigating the effectiveness of group psychotherapy intervention in sub‐threshold depression have shown varying results with differing effect sizes. A systematic review of randomised controlled trials of group psychotherapy in older adults with sub‐threshold depression was conducted to present the best available evidence in relation to its effect on depressive symptomatology and the prevention of major depression. Methods Systematic search of electronic databases and random effects model for meta‐analysis. Results Four clinical trials met the full inclusion criteria. Group cognitive behavioural therapy (CBT) is an effective intervention for reducing depressive symptoms in older adults with sub‐threshold depression in comparison to waiting list. Computerised CBT is at least as effective as group CBT in reducing depressive symptoms. The benefit of group CBT at follow‐up is not maintained. Group psychotherapy does not appear to reduce the risk of depressive disorder during follow‐up. There are fewer drop outs from group psychotherapy when compared with control conditions. The methodological quality of the studies and their reporting are sub‐optimal. Conclusions Group psychological interventions in older adults with sub‐threshold depression have a significant effect on depressive symptomatology, which is not maintained at follow‐up. Group psychotherapy does not appear to reduce the incidence of major depressive disorders. Copyright © 2012 John Wiley & Sons, Ltd.